2013
DOI: 10.3390/molecules18066469
|View full text |Cite
|
Sign up to set email alerts
|

89Zr, a Radiometal Nuclide with High Potential for Molecular Imaging with PET: Chemistry, Applications and Remaining Challenges

Abstract: Molecular imaging-and especially Positron Emission Tomography (PET)-is of increasing importance for the diagnosis of various diseases and thus is experiencing increasing dissemination. Consequently, there is a growing demand for appropriate PET tracers which allow for a specific accumulation in the target structure as well as its visualization and exhibit decay characteristics matching their in vivo pharmacokinetics. To meet this demand, the development of new targeting vectors as well as the use of uncommon r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 90 publications
6
94
0
3
Order By: Relevance
“…In contrast to that in the past decade, DFO has established its role in the context of 89 Zr-labelling [80][81][82][83][84]. 89 Zr was proposed as a diagnostic radionuclide for quantitating the biodistribution of radiolabelled antibodies.…”
Section: Desferrioxamine and Galliummentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to that in the past decade, DFO has established its role in the context of 89 Zr-labelling [80][81][82][83][84]. 89 Zr was proposed as a diagnostic radionuclide for quantitating the biodistribution of radiolabelled antibodies.…”
Section: Desferrioxamine and Galliummentioning
confidence: 99%
“…Standardized protocols have been established [90] making 89 Zr labelling for Immuno-PET applications ever more widely applicable. Several reviews have summarized the latest progress of 89 Zr-DFO-conjugated antibodies [82][83][84].…”
Section: Desferrioxamine and Galliummentioning
confidence: 99%
“…In recent years, the use of 89 Zr has increased significantly, particularly as a radiolabel for antibodies where a several-day half-life is required (Link et al, 1986; DeJesus and Nickles, 1990; Fischer et al, 2013; Holland et al, 2009; Meijs et al, 1992, 1997; Borjesson et al, 2006; Zhang et al, 2011; Bhattacharyya et al, 2013). The most common method for production of 89 Zr uses a cyclotron and the 89 Y(p,n) 89 Zr reaction (Sadeghi et al, 2012) and the cross sections for this production have been reported by many investigators including Levkovskii (1991); Wenrong et al (1992); Uddin et al (2005); Omara et al (2009); Sadeghi et al (2012); Kakavand and Taghilo (2013); and for the 89 Y(d,2 n) 89 Zr reaction by Zweit et al (1991).…”
Section: Introductionmentioning
confidence: 99%
“…DFO is a hydroxamic acid-based, acyclic chelator, which has been safely used in the clinic for the treatment of acute iron poisoning. It has also been shown invaluable for the development of 89 Zr radiopharmaceuticals, in particular in the context of immuno-PET as demonstrated in various preclinical and clinical studies (25). Because of the similarities of iron and gallium with regards to charge and ionic radii, DFO has also been reported for the chelation of 67/68 Ga (26,27).…”
Section: Glp-1 Receptor Imaging In Nuclear Medicine • Bauman Et Almentioning
confidence: 99%